Advancing Aluminum-Based Composite *Manufacturing: Leveraging TiO2 Reinforcement through Stir Casting Technique - Hussein Mohammed; Gundlapalle Rajesh; Kiran Kumar M.; Lakhanpal Sorabh; Kumar Parashar Ashish; Kaushik Abhishek (E3S Web of Conferences, 2024)
This study explores the advancement of aluminum-based composite manufacturing through the integration of titanium dioxide (TiO2) reinforcement using the stir casting technique. Aluminum alloy served as the matrix material, combined with ceramic reinforcement particles, melted at approximately 700°C within a muffle furnace. Through continuous stirring at 400 rpm for 10 minutes, ceramic particles were uniformly dispersed into the molten alloy, crucial for enhancing composite properties. The incorporation of 6.5% TiO2 via stir casting resulted in significant enhancements across multiple mechanical properties. Tensile strength improved by 23.67%, while hardness saw a remarkable increase of 38.9%. Additionally, fatigue strength exhibited a notable improvement of 26.67%, and wear resistance showed a substantial enhancement of 24.34%. The uniform dispersion of TiO2 particles throughout the composite material underscores the efficacy of the stir casting technique in achieving consistent improvements across various performance metrics. These findings hold promise for the development of high-performance aluminum-based composites tailored for diverse engineering applications.